Anthropometric and physical performance characteristics in African women football players: A prospective, cross-sectional pilot study - Nonhlanhla S. Mkumbuzi; Fidelis Chibhabha; Fredrick M. Govere; Matthew Chiwaridzo; Brenda Oulo (Central European Journal of Sport Sciences and Medicine, 2022)
Being injured is inherent to participating in football activities; therefore, prevention of injuries is crucial. This requires that the risk factors for injury be established. However, such studies are rarely conducted in women athletes in Africa. The study’s aim was to explore intrinsic risk factors for injury among African women football players using functional and musculoskeletal assessments. Participants (n=40) completed demographic questionnaires; upper and lower limb active range of motion (AROM); muscle endurance and functional movement screening (FMS™) assessed. Median age [Q1; Q3] was 24 [20; 27] years. Participants performed 20.5 [0; 30.5] push-ups and 28 squats [30; 38] in 60s; and held the prone elbow plank for 46.2s [30.6; 64.5]. Median FMS™ score was 12 [10; 13]; most players (n=27, 68%) could not execute a proper deep squat. Most players (70%; n=28), were able to properly perform the in line lunge but scored poorly in the shoulder mobility domain of the FMS™, with 73% (n=29) scoring ≤1. Players with a history of injury had lower FMS™ total (p=0.02). Overall, participants presented with low muscle endurance and movement imbalances, which might predispose them to injury. Hence, strength and conditioning measures should be instituted in this population to prevent injuries.